The Correlation between Self-Confidence of the Undergraduate EFL Students and Their Speaking Achievement - Rizkie Mauly Audina; Amalia Hasanah; Deta Desvitasari (Yayasan Karinosseff Muda Indonesia, 2021)
The aims of this study were to investigate whether there is a correlation between Self-Confidence with EFL students’ speaking achievement. The participants of this study were the Undergraduate EFL Students of UIN Raden Fatah Palembang. purpose. The participants that were chosen can meet certain criteria from this study. In this study, the student’s self-confidence and their speaking achievement are correlated. Therefore, in order to know the students’ speaking achievement, a group of students who had already taken the informal speaking courses from the population were considered as the sample. Nonetheless, most of the third semester students have already finished the informal speaking class on last semester and they are on the next level of speaking class on this semester. Quantitative method was used in this study. The data gained from self-confidence questionnaire and the list of students’ speaking achievement was analyzed by using SPSS. The result of the study showed that there is no significant correlation and there is no significance influence between self-confidence of the undergraduate EFL students with their speaking achievement. The researchers of this study recommends other researchers to make sure the respondents are in well condition such as feeling comfortable while taking the data. Furthermore, it is recommended that other researchers to do and to extend more variables in order to reveal any aspects that can support and enhance the quality of researches in speaking skill.